Highly efficient deep-blue organic light-emitting diodes based on pyreno[4, 5-d]imidazole-anthracene structural isomers. Issue 33 (9th August 2019) - Liu, Hui; Kang, Liangliang; Li, Jinyu; Liu, Futong; He, Xin; Ren, Shenghong; Tang, Xiangyang; Lv, Changli; Lu, Ping
Abstract : By integrating PyI with anthracene, two high-efficiency blue emittersC-BPyIA andN-BPyIA are obtained. Especially, N-BPyIA exhibits decent device performance with an EQEmax of 7.67% in the deep blue region. Abstract : High-efficiency deep-blue luminophores, especially those satisfying the National Television Standards Committee (NTSC) blue standard Commission Internationale de l'Éclairage (CIE) coordinates of (0.14, 0.08), are vital for full-color displays and solid-state illumination. However, deep-blue luminescent materials with efficient photoluminescence quantum yields ( φ PL s) and high external quantum efficiencies (EQEs) over 5% remain very limited. Imidazole has shown great potential in optoelectronic fields owing to its ambipolar nature. Combining imidazole with rigid aromatic rings, such as naphthalene, phenanthrene and pyrene, could effectively enlarge the π-electronic delocalization, reduce non-radiative transitions of molecules and ensure high φ PL s in the solid-state. Herein, two symmetrically twisted pyreno[4, 5- d ]imidazole-anthracene structural isomers, 9, 10-bis(4-(10-phenyl-9 H -pyreno[4, 5- d ]imidazol-9-yl)phenyl)anthracene (N-BPyIA ) and 9, 10-bis(4-(9-phenyl-9 H -pyreno[4, 5- d ]imidazol-10-yl)phenyl)anthracene (C-BPyIA ), have been designed and synthesized by connecting one anthracene group with two pyreno[4, 5- d ]imidazole groups at the N1 and the C2 position, respectively. They both show high φ PL s in neat films (46% forN-BPyIA and 54% forC-BPyIA ), good thermal stabilities ( T d > 541 °C), and appropriate energy levels for carrier injection.N-BPyIA shows better performance thanC-BPyIA when applied in OLEDs. The non-doped device based onN-BPyIA shows sky blue emission with CIE coordinates of (0.22, 0.31), achieving a high EQE of 5.63% with a low efficiency roll-off. In particular, a doped device with better performance is further realized, providing an EQE of 7.67% and deep-blue emission (CIE (0.15, 0.10)), which is very close to the NTSC standard. Such high OLED efficiency may be ascribed to triplet energy harvesting by triplet–triplet annihilation. And to our best knowledge, this is one of the best outcomes of deep-blue imidazole-based fluorescent OLEDs. The results also pave the way for a new type of high-efficiency deep-blue organic luminescent materials regulated by structural isomerization.